Textiles and personal adornment in the Arabian Peninsula: papers from the special session of the Seminar for Arabian Studies held on 29 July 2016 - Martinez, Aisa (Proceedings of the Seminar for Arabian Studies, 2017)
Textiles, dress, and personal adornment have been key to the societies of the ancient, historic, and modern Arabian Peninsula, but there has been little academic attention paid to their importance. The last major conference to discuss the social history of textiles, dress, and personal adornment of the Middle East region took place at the School of Oriental and African Studies (SOAS), University of London in the late 1990s. This culminated in the publication Languages of dress in the Middle East (Lindisfarne-Tapper & Ingham 1997), one of the most useful resources for those presenting papers at the Special Session on ‘Textiles and personal adornment in the Arabian Peninsula’. The aim of the 2016 Special Session was to reintroduce the study of textiles and personal adornment into the wider discussions of the Seminar for Arabian Studies and continue the scholarship on the language of dress, textiles, and personal adornment specific to the Arabian Peninsula in the past, present, and future.